Hubungan Antara Motivasi, Sikap, dan Kecerdasan Adversitas dengan Hasil Belajar Biologi Peserta Didik Kelas XI SMA - Hasniar, Hasniar; Hala, Yusminah; Syamsiah, Syamsiah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to analyze the relationship between learning motivation, learning attitude, and adversity quotient with biology learning outcomes of eleventh grade students at SMA Negeri 1 Makassar. The research method used is ex-post facto with a correlational nature. The population of this study consists of all students of SMA Negeri 1 Makassar totaling 1212 students. The sample of the study is the eleventh grade science class determined using the Slovin formula, with a sample size of 132 students. Data collection involved instruments measuring learning motivation, learning attitude, and adversity quotient comprising 90 items of statements and documentation. The research findings revealed a correlation coefficient of 0.809, indicating a strong relationship between the variables.